1993
DOI: 10.1029/93gl00684
|View full text |Cite
|
Sign up to set email alerts
|

Sharpness of the mantle discontinuities

Abstract: Seismic estimates of sharpness of the mantle discontinuities are important for constraining models of composition and temperature in the deep Earth but these data are difficult to obtain. We explore a possibility to determine sharpness of the major mantle discontinuities (those at depths around 400 and 650 km) from the broad‐band records of phases converted from P to S underneath the receiver. Our estimates are obtained from a comparative analysis of waveforms of the converted phases and those of the P waves i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…Petersen et al (1993b) found a sharper 410 (5-7 km) than 660 (20-30 km) from Ps conversions at several broadband stations in different regions. They observed that both discontinuities (410 and 660) were < 4 km sharp.…”
Section: Sharpness Of 410 and 660mentioning
confidence: 80%
“…Petersen et al (1993b) found a sharper 410 (5-7 km) than 660 (20-30 km) from Ps conversions at several broadband stations in different regions. They observed that both discontinuities (410 and 660) were < 4 km sharp.…”
Section: Sharpness Of 410 and 660mentioning
confidence: 80%
“…The modulations originate from the density jumps at distances h 1 = 410 km (by 5%) and at h 2 = 660 km (by 10%) from the surface of the Earth. These density changes occur over depth interval less than 5 km [19], [20], which is much smaller than the oscillation length. Therefore the jumps break adiabaticity.…”
Section: Effect Of the Be Neutrino Line Widthmentioning
confidence: 99%
“…2 (right). Potentla energy d~agraln for HI and I. obtaned from (15)(16)(17)(18). The short and long arrows on the eft ~ndicate the lnechanisln for-controlling the exc~tat~on of HI.…”
mentioning
confidence: 99%
“…Figure 1 shows the three-photon photoionization spectrum obtained with the U V beam. The rotational structure in the HIsignal results from 2+ 1 resonance-enhanced multiphoton ionization (REMPI) of the b3112 and b3111 Rydberg states (15). The b 3 n l state is strongly predissociated and produces I atoms that are responsible for the peak seen in the Ispectrum near 351.8 nm.…”
mentioning
confidence: 99%